Passive flow control study in a convoluted intake using Stereo Particle Image Velocimetry - Tanguy, Geoffrey; MacManus, David G.; Zachos, Pavlos K.; Gil-Prieto, Daniel; Garnier, Eric (AIAA, 2016)
The ability of vortex generators (VG) to reduce the unsteady distortion at the exit plane of an S-duct (AIP) is investigated. The 3 components of the velocity at the AIP were measured using a Stereo Particle Velocimetry system with high spatial resolution. This enabled an assessment of the synchronous swirl distortion at the duct exit. A total of nine VG cases have been investigated with a systematic variation of key design variables. Overall the VGs change the duct secondary flows and separation and are able to substantially restructure the flow field at the AIP. The pressure distortion could be reduced up to 50% and a reduction in pressure loss of 30% was achieved for the mean flow field. The VGs have a substantial influence on the unsteadiness of the flow field with a reduction in peak swirl unsteadiness of 61% and an overall reduction of unsteady swirl distortion of 67%. They also suppress the primary unsteady flow switching mechanism of the datum configuration which is associated with the oscillation of bulk and twin swirl regimes. Consequently, extreme events which leads to high swirl intensity are suppressed which lower by 45% the maximum swirl intensity for the VG cases.